Instruments and materials for digital manufacturing in architecture - Cesare Sposito; Francesca Scalisi (Agathón)
The article describes tools and materials available today for digital manufacturing in architecture, offering a wide overview of 3D printing techniques and how it could revolutionize the construction world with important come backs and not only technical ones. From the concept of mass customization to the creation of the Fab Lab, from Contour Crafting to D-Shape technology and to the WASP project, we are witnessing a radical rethinking of the architectural process, but also a continuous research on the materials.